Assessment Of Lecturer Performance On Social Competencies At Ibn Sina Islamic High School - Hazriyanto, Hazriyanto; Afridola, Sri; Ibrahim, Badaruddin (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2019)
Performance assessment instruments of social competence perceptional built and developed based on theories of performance assessment of competence and on the basis of previous research within and outside the country. This research based on the theory of performance assessment of lecturers upon social competence posited perceptional performance lecturer assessed competency and one of them is social competence, This assessment involves assessment of the 12 items are built. Early research involving 34 people respondents a lecturer at an Islamic High school environment (STAI) Ibnu Sina Batam. The validity of the instrument is determined by the validity of the item and the person. Instruments Questionnaire given to 34 people. The number of logit items from the MEAN and SD. In view of the value of the person whose value reliability of 0.78 and 0.89 reliability item can be concluded that the consistency of the answers of the respondents on a nice and quality than on items in the instrument of social competence good lecturer. The instrument is built and developed meet the characteristics of an appropriate instrument with the rasch model as an instrument of performance appraisal of social competence perceptional lecturer